Response of different cultivars of apricot to the postharvest application of methyl jasmonate - Raja, Jeelani; Masoodi , F A (Journal of Postharvest Technology, 2023)
Apricots have restricted marketability and commercial viability due to their high degree of perishability, which generally leads to huge post harvest losses. A study was conducted to evaluate the physical and geometrical characteristics of different cultivars of apricots (CITH-1, CITH 2, Erani, Harcot, and Tilton) and to assess the effect of post-harvest application of methyl jasmonate (MeJ; 0.1 mmolL-1 and 0.2mmolL-1) on its quality, enzyme-specific activities, and shelf life. Apricots were dipped in different concentrations of MeJ and then stored at a refrigerated temperature (1 ± 1oC, RH 80-85 %) for 42 days. Apricots treated with MeJ (0.1 mmolL-1) followed by refrigeration significantly (p < 0.05) retained higher levels of antioxidant activity and total and reducing sugars compared to MeJ (0.2 mmolL-1) and the control. In terms of reducing decay percentage, weight loss, fruit firmness, as well as inhibition of enzyme activity, both MeJ treatments were significantly (p < 0.05) effective in preserving the quality and extending the shelf life of apricots. According to the findings of this study, post-harvest application of MeJ (0.2 mmolL 1) can be applied to preserve the quality of fresh apricots and their bioactive constituents in refrigerated storage for up to 42 days.